ANALISIS DESAIN IKLAN DENGAN PENDEKATAN BUDAYA MENURUT KRITERIA EVALUASI KONSUMEN DI KOTA MATARAM (STUDI KASUS IKLAN TELKOMSEL BERNUANSA BUDAYA SASAK) - Lalu Adi Permadi; Muhammad Ilham; G. A. Sri Oktariyani (Master of Management, Mataram University, 2017)
The purpose of this study is to determine suitable design of the Telkomsel culture approach ad by using the evaluation criteria the consumer of Sasak ethnic in Mataram. Methodologically, to prove the purpose of the study was using Mixed Methods Research that consisting of Focus-Group Research, and in-depth interviews,. The results of this study showed that the ideal design of Telkomsel's advertising design nuanced cultural according to consumers' evaluation criteria with the following attributes 1) Color; 2) Picture: Art and Cultural Events Other Sasak; 3) Information Features and Amenities: Features And major addition; 4) slogan: Relating to Identity Lombok Island, 5) information Price: Clearly in Any feature Promoted; 6) Size: Extra Large; 7) Media: Advertising Signage / Billboards Or Banners and 8) ad Location: Population in Each place Solid.Keywords: design, advertising, culture approach, consumer evaluation criteria